Omental infarction in children misdiagnosed as acute appendicitis. Issue 3 (July 2015) - Catania, Vincenzo D.; di Giacomo, Vincenza; Bonomo, Roberta; Guarino, Nino
Abstract : Omental infarction (OI) is a rare cause of acute abdomen in children. It is found in 0.1–0.5% of pediatric patients undergoing abdominal exploration for the suspect of acute appendicitis. OI is considered a self-limited entity, and conservative management should be considered. This approach implicates computer tomography scan radiation exposure, prolonged hospitalization, and prolonged analgesic and anti-inflammatory therapy. In contrast, surgery allows immediate pain resolution with low complication rate. We present our experience with two cases of pediatric acute abdomen due to OI, misdiagnosed as acute appendicitis, which were successfully treated surgically.